Didactic Laws Methodological Basis of Modernization of the Educational Process - Shodmonova Zilola Bozorovna (International Journal on Integrated Education, 2022)
Mankind's centuries-old experience in building the state and society has led to the development of advanced approaches to the regulation of social relations on the basis of new approaches. The essence of these approaches in recent years has been expressed in general terms using the concept of "modernization". This modernization is comprehensive, preserving and enriching the best traditions of teaching and educating the individual, fully covers all areas of the education system and serves to meet the needs of society in the training of qualified professionals